Efficacy of tamarind leaf infusion (Tamarindus indica L.) as an antidiarrheal agent in mice - Ratna Kristiani Nababan; Lina Noviyanti Sutardi; Anisa Rahma; Aulia Andi Mustika (Current Biomedicine, 2025)
Background Bacground Tamarind (Tamarindus indica L.) is an herbal plant that is used to treat various diseases, but there has been no scientific research on the activity of tamarind leaf infusion as an antidiarrheal.